The 15th Anniversary of the Seminar on the History of Higher School in St. Petersburg - T. V. Kostina (Высшее образование в России)
University teachers in Russia have a period of increasing pedagogical and paper load. In this situation it is important to offer an environment,  preserving and developing their research skills, providing a possibility of  discussing their results in an audience of expert and concerned colleagues. A  thematic seminar as a form of such environment in many respects has  advantages over conferences, with their strict rules of reports and  discussions. The seminar on the history of higher school in St. Petersburg for  15 years has been an informal platform for reports and discussions on the history of higher education not only in St. Petersburg, but also in the  territories of the former Russian Empire and the Soviet Union. Reports,  presented at the interdisciplinary seminar, deal with the educational policy,  the history of educational institutions, the methodology of studying the  history of higher education, the study of archival collections of educational  institutions, etc. Over the past five year 18 sessions have been held, 4 of  them – in the form of problematic round tables; overall 30 reports were  presented.